La prex eucarística de la Traditio Apostolica d’Hipòlit de Roma i la regula de l’oració cristiana de l’ Ambrosiaster = The Eucharistic prex of Hippolytus of Rome’s Traditio Apostolica and the regula of Ambrosiaster’s Christian prayer - Gros i Pujol, Miquel S. (Miscel·lània litúrgica catalana, 2023)
The text of the Traditio Apostolica and its attribution to Hippolytus of Rome are still matters of controversy. In this paper we propose a new consideration of the text on the basis of the study of the Eucharistic prex, pertaining to a community with marked Eastern influences which was established in Rome and which, led by Hippolytus, sought to legitimise his apostolicity.